Operation Strategy Formulation in GKSI Boyolali Milk Treatment Industry - Zachary, Reyhan; Yudoko, Gatot (Journal of Business and Management, 2016)
Abstract- GKSI (Union of Indonesian Dairy Cooperatives) Boyolali is milk treatment industry currently specializing in condensed milk and focus to do B2B as contract manufacturer. They faced pressure on profit margin due to tighter competition and increasing raw material and utility cost. The company did not success on fulfilling market requirement and managing their resources affecting to uncompetitiveness on their business. The purpose of this research is to propose strategy formulation to improve their performance through corporate, business, operation strategy. Conceptual model to be used in this research is strategic management model about strategy hierarchy and operation strategy model by Slack and Lewis. The data to support analysis were collected through in-depth interview with people in the company, observation, historical data of the company, and information from public news. Corporate strategy formulation began by doing external and internal analysis, then summarizes it into SWOT. Then, it would use IFAS-EFAS, Grand Matrix, GE Matrix, and TOWS Matrix to determine directional strategy. Business strategy would use Porter Competitive Strategy. As final output, operation strategy formulation would determine performance objectives that considered pivotal for the company. Then, it continued by determining the excellent strategy through operation strategy matrix with prioritizing the certain area that become critical structural and infrastructural decision. In corporate level strategy, the direction of company is stability and selective investment. Business strategy that suit the most for their current condition and capability is differentiation. With quality and speed are the most pivotal performance objectives, the company should focus to acquire cooling technology for production process (structural decision), product and service development and improve standardization on production (infrastructural decision). On implementing those strategies, they could try to install tubular heat exchanger, improve customization level, and improve HACCP (Hazard Analytical Critical Control Point) system implementation in production process.Â Keywords: Milk Treatment Industry, Contract Manufacturer, Operation Strategy, Structural and Infrastructural Decision